Anisotropic thermal conductivity of polypropylene composites filled with carbon fibers and multiwall carbon nanotubes. Issue 11 (23rd June 2014) - Mazov, Ilya; Burmistrov, Igor; Il'inykh, Igor; Stepashkin, Andrey; Kuznetsov, Denis; Issi, Jean‐Paul
<x xml:space="preserve">Abstract</x> Polypropylene‐based composites filled with carbon fibers and multiwall carbon nanotubes were produced by coagulation precipitation technique. Composite articles were produced by conventional injection molding technique. It was shown that the addition of carbon nanotubes (10% of total amount of carbon fibers) results in significantly increased anisotropic thermal conductivity of the composite due to formation of thermal conductive bridges between carbon fibers, which are oriented during molding. The addition of CNTs has a significant effect with more than a 50–70% increase of both the axial and transverse thermal conductivity of the composite. Produced composites were used for injection molding of polymeric radiators for LED lamps, showing sufficient heat dissipation efficiency allowing using them for industrial application in the field. POLYM. COMPOS., 36:1951–1957, 2015. © 2014 Society of Plastics Engineer